2020
DOI: 10.1097/scs.0000000000006092
|View full text |Cite
|
Sign up to set email alerts
|

The Accessory Parotid Gland and its Clinical Significance

Abstract: Purpose: The accessory parotid gland is a collection of salivary tissue separate from the main parotid gland. When present, it may complicate parotidectomies, promote parotitis, and serve as a potential site for benign and malignant lesions to arise. The aim of this study was to provide a comprehensive and current overview of the anatomy of the accessory parotid gland, as there is a wide discrepancy in the literature regarding its prevalence. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
8
2
7
Order By: Relevance
“…Heterogeneity exists in the prevalence and location of the APG in the population, as more than one APG may be found unilaterally, adjacent to a single PG, or deviate from its expected location (18). The prevalence of the APG in our study was 23.53%, which was lower than the 33.8% prevalence found in a recent meta-analysis in Asia (18). In addition, a higher prevalence was observed in male compared to female patients.…”
Section: Discussioncontrasting
confidence: 86%
“…Heterogeneity exists in the prevalence and location of the APG in the population, as more than one APG may be found unilaterally, adjacent to a single PG, or deviate from its expected location (18). The prevalence of the APG in our study was 23.53%, which was lower than the 33.8% prevalence found in a recent meta-analysis in Asia (18). In addition, a higher prevalence was observed in male compared to female patients.…”
Section: Discussioncontrasting
confidence: 86%
“…Our review of the literature identified reports of variation in anatomy of the submandibular gland to be rare. Fewer than 15 cases of accessory submandibular glands have been reported in our review of the literature, whereas accessory lobes to the parotid gland are common and have been in 32.1% of cases examined [1 , 2] .…”
Section: Discussionmentioning
confidence: 75%
“…Anatomic variation of submandibular glands is a rare finding, unlike the more commonly variable parotid gland [1] . Abnormal findings have been characterized by unilateral duplications of submandibular ducts with or without an accessory submandibular gland [2] .…”
Section: Introductionmentioning
confidence: 98%
“…Cabe resaltar la importancia de los adenómeros dentro de las glándulas salivales, ya que, están extremadamente polarizadas y delimitadas por una membrana de plasma con un dominio basolateral que se encuentra separados por uniones estrechas. 6,18,26,28,30,31 Éstos son responsables de la producción y secreción de gránulos secretores que contienen componentes salivales funcionales como amilasa, mucinas e inmunoglobulinas. 13,19,28,29,32,33 Varios autores indican que las células mioepiteliales son delgadas, contráctiles, en forma de huso y que están intercaladas entre las células epiteliales acinares y pequeños conductos.…”
Section: Histología De La Glándula Parótidaunclassified